Penser & construire avec les déblais de terre, ressource principale de nos villes.Le cas de Cycle Terre, première fabrique européenne de matériaux issue du recyclage des terres du Grand Paris - Paul-Emmanuel Loiret (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
In the world’s major cities, millions of tons of soil are excavated each year as part of development and construction work. This natural excavated soil, considered in the regulatory sense as waste, is mostly directed to storage facilities (landfills). In Sevran, the Cycle Terre project aims to recycle part of this noble and local resource to build the « Grand Paris » of tomorrow while targeting the formation and evolution of regulations allowing the implementation of ad hoc construction systems on an urban scale. The construction of the « Earth Cycle Factory », funded by Europe and the Ile de France Region, will produce from September 2021, in a short circuit, a range of eco-sourced materials from this recovered resource such as clay panels, mud bricks or wall plaster. These new material sectors should lead to a change in the paradigm of architectural and urban design.